Extracorporeal Membrane Oxygenation for COVID-19: Collaborative Experience From the Texas Medical Center in Houston With 2 Years Follow-Up. Issue 12 (21st September 2022) - Akkanti, Bindu; Suarez, Erik E.; O'Neil, Erika R.; Rali, Aniket S.; Hussain, Rahat; Dinh, Kha; Tuazon, Divina M.; MacGillivray, Thomas E.; Diaz-Gomez, Jose L.; Simpson, Leo; George, Joggy K.; Kar, Biswajit; et al.
Abstract : Patients with severe refractory hypoxemic respiratory failure may benefit from extracorporeal membrane oxygenation (ECMO) for salvage therapy. The Coronavirus disease 2019 (COVID-19) pandemic offered three high-volume independent ECMO programs at a large medical center the chance to collaborate to optimize ECMO care at the beginning of the pandemic in Spring 2020. Between March 15, 2020, and May 30, 2020, 3, 615 inpatients with COVID-19 were treated at the Texas Medical Center. During this time, 35 COVID-19 patients were cannulated for ECMO, all but one in a veno-venous configuration. At hospital discharge, 23 (66%) of the 35 patients were alive. Twelve patients died of vasodilatory shock (n = 9), intracranial hemorrhage (n = 2), and cannulation-related bleeding and multiorgan dysfunction (n = 1). The average duration of ECMO was 13.6 days in survivors and 25.0 days in nonsurvivors ( p < 0.04). At 1 year follow-up, all 23 discharged patients were still alive, making the 1 year survival rate 66% (23/35). At 2 years follow-up, the overall rate of survival was 63% (22/35). Of those patients who survived 2 years, all were at home and alive and well at follow-up.